2021
DOI: 10.52114/apjhad.937206
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Pounding Between Adjacent Buildings: A Review

Abstract: The collision between adjacent buildings with an insufficient seismic separation distance has been reported after earthquakes. This collision between adjacent buildings, commonly referred to as earthquake-induced pounding, entails huge damages to the involved buildings. The main cause of damage was interpreted to the developed impact forces between colliding buildings. The intensity of the impact force relies on many factors, therefore, a significant research effort was found to address this issue from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For buildings with insufficient gap distance, collisions are inevitable. The collision between adjacent structures, also known as the pounding phenomena, significantly changes the global response of the collided buildings namely the loading path and, therefore, the collapse mechanisms [1][2][3]. Devastating earthquake events leave huge life and economical losses, particularly for those structures with inherited seismic vulnerability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For buildings with insufficient gap distance, collisions are inevitable. The collision between adjacent structures, also known as the pounding phenomena, significantly changes the global response of the collided buildings namely the loading path and, therefore, the collapse mechanisms [1][2][3]. Devastating earthquake events leave huge life and economical losses, particularly for those structures with inherited seismic vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Over 50 years, a vast body of literature addressing the pounding effects on the structural response has been found based on the provided lessons from major earthquakes (e.g., see [1,7] among others). These studies were found on different scales; from studying the impact phenomena on the global performance of the adjacent structures with a limited number of ground motions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations after many earthquake indicates that local damage at the interaction point is due to insufficient separation between buildings. Therefore, major efforts have been directed towards the problem of seismic analysis of buildings using different modeling techniques (Mohamed et al 2021).…”
Section: Introductionmentioning
confidence: 99%